Metal exposure in respirable & inhalable dust by the locality of coal-fired power plant - Mohd. Din, Shamzani Affendy; Nik Yahya, Nik Nurul Hidayah; Othman, Rashidi (Malaysia Institute of Planners, 2018)
The surrounding area of the coal-fired power plant is mostly exposed to its chemical contents. The world has witnessed multi cases relevant to mortality due to overexposure to coal materials. However, these factors have not been faced by the Malaysians. Still, it is significant to monitor and control the coal-fired power plant exposure. This research aims to identify the dominant metal within the radius of a coal-fired power plant combustion source point. The inhalable and respirable dust are being collected then analysed and calculated its Permissible Exposure Limit (PEL). Later, health impact knowledge is being synchronized with the obtained data. Hence, built environment at the radius 5km, 10km, 15km and 20km was being observed as well as inhalable and respirable dust. The data was analysed using the ICPMS (Nexion 300x) to trace the concentrations of metals. The metals include Ba, Cr, Cu, Fe, Mn, Ni, Pb, V, and Zn. Generally, the results showed that the total of respirable towards inhalable dust ratio of metal concentration found at Manjung was 88.62%. The highest concentration found in Iron was at 4.710 ng m-3 for respirable dust and Zinc for inhalable dust at 7.387 ng m-3; thus, claiming both Iron and Zinc as the dominant metals in Manjung. The pattern of metals concentration found in this research proven that the FGD and ESPs application in Manjung coal-fired power plant contributed to reducing the airborne particles emissions. However, the PEL calculations showed exceeding limits of metals found on site. Hence affecting the human respiratory, cardiovascular and nervous systems. Therefore, new research in developing the policy for the construction of the coal-fired power plant, especially within the radius of a residential and public area are in significant need.